Impact tests and pre blast tests predictions - Del Linz, Paolo (Nanyang Technological University, 2020)
In this context, it was decided to consider the performance of steel vertical structures, composed of several steel universal beam (UB) sections welded together, with additional protective steel plates on each face. Additionally, a steel-concrete sandwich panel type was also included. It was decided that they would be included in the study to assess their performance with realistic charges. To fully consider the behaviour of these structures and to inform modelling techniques to be used to facilitate their design, it was decided to conduct a series of experiments, including both impact and blast tests. These would then be used to validate detailed numerical models, with a special attention to developing blast tests prediction capabilities.